Ratio Decidendi Hakim dalam Menjatuhkan Pidana terhadap Tindak Pidana Merintangi Kegiatan Pertambangan: Studi Putusan Kasasi Nomor 5690 K/PID.SUS/2025 - Solihin, Solihin; Nashriana, Nashriana; Irsan, Irsan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research analyzes the application of criminal sanctions for the offense of obstructing lawful mining activities in Indonesia through a study of Supreme Court Decision Number 5690 K/Pid.Sus/2025. Mining activities are a strategic sector that significantly contribute to national economic development and regional growth, yet they are often accompanied by social conflicts that lead to criminal charges against individuals or communities under Article 162 of Law Number 3 of 2020 on Mineral and Coal Mining. In practice, the proportionality and effectiveness of criminal sanctions imposed by the courts remain debatable, particularly when compared to the substantial economic losses suffered by mining companies and the broader objectives of criminal law enforcement. This study aims to examine the judges’ ratio decidendi in imposing criminal sanctions and to formulate a more appropriate and future-oriented sanction model that ensures legal certainty, justice, and legal utility. The research employs a normative juridical method using a statutory approach, a case approach, and a futuristic approach. Primary legal materials consist of legislation and court decisions, while secondary legal materials include legal doctrines, academic journals, and relevant scholarly literature. The results indicate that although the Supreme Court consistently applies Article 162 as the legal basis for criminal liability, the sanctions imposed tend to be relatively lenient and insufficiently proportional to the magnitude of the losses incurred by mining companies. Such leniency weakens the deterrent effect of criminal law and may undermine the credibility of law enforcement. Therefore, this study proposes that future criminal sanctions should adopt a more proportional, multidimensional, and restorative approach, balancing the protection of lawful mining investments with the protection of community rights and environmental sustainability to achieve substantive justice in mining criminal law enforcement.